Solar-powered cold-storages and sustainable food system transformation: Evidence from horticulture markets interventions in northeast Nigeria - Takeshima, Hiroyuki; Yamauchi, Futoshi; Bawa, Dauda; Kamaldeen, Salaudeen O.; Edeh, Hyacinth O.; Hernandez, Manuel A. (International Food Policy Research Institute, 2021)
Modern cooling technologies that utilize renewable energy sources have been increasingly recognized as a promising tool to address a multitude of challenges emerging in progressively complex food systems in developing countries. When provided as cold-storages inside horticulture markets, cooling technologies can potentially contribute to improved quality of products and strengthened vertical linkages. Knowledge gaps about the actual impacts of these technologies in developing countries remain, especially in Africa south of Sahara (SSA). This study partly fills this knowledge gap by providing evidence from the evaluation of recent interventions in northeast Nigeria in which 7 small solar-powered cold-storages were installed across 7 horticulture markets. Combinations of difference-in-difference and variants of propensity-score-based methods suggest that using cold-storages significantly increased horticulture sales volumes and revenues of market-agents. Back-of-the-envelope calculations indicate that increased net revenues for market-agents may be sufficiently large to recoup the investments and operating costs of cold-storages within a reasonable time frame. Using cold-storage also reduced the share of food loss and lengthened the products' shelf-life, while raised prices received by both market-agents and farmers, which were associated with improved product quality, expanded value-adding activities by market-agents, and increased use of advance payments. We find no evidence of negative spillover effects inside horticulture markets. Finally, additional food-science experiments confirm that cold-storages preserve original physical and nutritional qualities of key horticultural products several days longer than products stored under ambient temperature.